The genetics of tiger pelage color variations - Xu, Xiao; Dong, Gui-Xin; Schmidt-Küntzel, Anne; Zhang, Xue-Li; Zhuang, Yan; Fang, Run; Sun, Xin; Hu, Xue-Song; Zhang, Tian-You; Yang, Han-Dong; Zhang, De-Lu; Marker, Laurie; et al. (Cell research, 2017)
Dear Editor, The tiger （Panthera tigris） is most recognized for its dark stripes against an orange background. Less well known are three other pelage color variants： white, gold- en and stripeless snow white （Figure 1A）. The white tiger is a polymorphism that was first seen among wild Bengal tigers （P t. tigris） in India, with white fur and se- pia brown stripes [ 1 ]. The golden tiger, also first sighted in the jungle in india, has a blonde color tone with pale golden fur and red-brown rather than black stripes [2].